(-)-6 alpha-Hydroxy polyanthellin A - a novel antifouling diterpenoid from the Indian soft coral Cladiella krempfi (Hickson) - Mol, V. P. Limna; Raveendran, T. V.; Parameswaran, P. S.; Kunnath, R. J.; Rajamohanan, P. R. (Canadian Journal of Chemistry-Revue Canadienne De Chimie, 2011)
Bioassay-guided purification of methanol extract of the soft coral Cladiella krempfi (Octocorallia: Alcynocea) yielded a novel eunicellin-type diterpenoid, (-)-6 alpha-hydroxy polyanthellin A (1), active against the cyprids of the fouling barnacle, Balanus amphitrite (EC(50) 9.02 mu g/mL; LC(50) 36 mu g/mL; and therapeutic ratio = 4). The structure of compound 1 was determined from its spectral data, including IR, NMR (1D and 2D NMR), and mass spectra.
Keywords: antifouling; Balanus amphitrite; biofouling; Cladiella krempfi; diterpenes

Active pharmaceutical ingredient (api) from an estuarine fungus, microdochium nivale (Fr.) - Bhosale, Siddharth H.; Patil, K. B.; Parameswaran, P. S.; Naik, C. G.; Jagtap, T. G. (Journal of Environmental Biology, 2011)
Various marine habitats sustain variety of bio-sources of ecological and biotech potentials. Pharmaceutical potential compound Cyclosporine A was reported from marine fungus Microdochium nivale associated with Porteresia coarctata, a marine salt marsh grass from mangrove environment distributed along the Central West Coast (CWC) of India. This study involves association of M. nivale with P. coarctata plant, fermentation conditions, purification of Cyclosporine A, chemical characterization etc. Its antifungal inhibition and MIC (Minimum inhibitory concentration) against Aspergillus strains (A. niger, A. japonicus, A. fresenii), yeasts and dermatophytes (Candida sp., Cryptococcus neoformans, Trichophyton mentagrophytes, T tonsurans, T violaceum, Microsporium gypsum and Fusarium sp.) were evaluated. However, the MIC against A. japonicus, C. neoformans, Candida sp. and T. tonsurans were confirmed to be as low as 12.5-25 mg disc(-1). The antifungal properties of Cyclosporine A against Aspergillus species, yeast and dermatophytes revealed that Cyclosporine A would be a potential compound for life threatening diseases caused by above fungi in both human and animals. Furthermore, we have reported herewith another source of Cyclosporin A derived from filamentous fungus, M. nivale. occurring in marine environment.
Keywords: antifungal; Cyclosporine A; Estuarine environment; Microdochium nivale